Guerrilla statesmanship: constitutionalizing an ethic of dissent - Newswander, Chad B. (2015)
According to judicial precedents, administrators informed by their expertise can speak on issues of public concern under First Amendment protections. In one sense, they could dissent by working against their employers in an attempt to direct issues of public concern through an educational function. The power to act like a statesman in raising such issues allows administrators to lead from behind and in front, as long as certain judicial thresholds are met. However, the U.S. Supreme Court recently moved to tighten the scope of such activity. This article assesses how an ethic of dissent has been translated into a constitutional perspective that at first was moderately constrained and later became very restricted. While the move to limit an ethic of dissent provides necessary constraints, it also may have weakened administrators ability to perform necessary statesmanship acts rooted in guerrilla government to achieve the common good. - Reproduced.
Keywords: Public administration